RESEARCH ON THE INFLUENCE OF THE OPERATING MODES OF COMBINE HARVESTER’S TRANSPORTATION LINES ON THE QUALITY OF GRAIN THRESHING - Yakhin, S. V.; Burlaka, O. A. (Scientific Progress & Innovations, 2020)
The aim of the study is to develop recommendations for reducing grain losses based on the analysis of experimental data on the characteristics of flows during its transportation by the scraper elevators of a combine harvester. Primary experimental data were obtained using capacitive-wave sensors for grain threshing. For carrying out experimental studies, a combine harvester KZS-9-1 "Slavutych" was chosen, which was equipped with a grain threshing sensor DNZ-01. To control the productivity of the grain-bearing elevators, it was equipped with a grain re-threshing sensor DDZ-01. An on-board computer was used to record data on the productivity of the grain flow of the elevator. The grain threshing sensor and the grain rethreshing sensor according to the functional diagram are made in the same way but differ in geometric parameters. This is due to the design features of the grain transport lines of the combine, and is considered as the main part of the experimental equipment for controlling the flow of agricultural materials. The measurement results were processed using the methods of mathematical and statistical analysis using applied computer programs. The performance of the grain and spike elevator of the KZS-9-1 "Slavutych" combine was measured in the field using sensors for threshing and final threshing of grain when harvesting winter wheat by direct combining with an average yield of 4.8 t/ha, grain moisture – 12…13%, straw content – 1 : 1 and the upright vegetation cover of grain fields. The site was chosen as a strip of a field with a width of 14 m and a length of 1000 m, had clogged areas and liquefied crops, that is, the real working conditions of the combine. When comparing the experimental flow characteristics of the productivity of the grain and grain elevators of the combine with the well-known parameters of the quality of technological adjustments of the thresher, at the initial stage, free grain in the final threshing line was found. At the same time, the average productivity of grain transportation in the threshing line was 3…4 kg/s, in the final grinding line – 0.05…0.15 kg/s. By changing the technological adjustments of the thresher, no possible flow of the grain heap in the final threshing line was achieved – 0.04…0.08 kg/s, which increased the productivity of transporting grain to the bunker to 3.1…4.2 kg/s. Such correction of the technological process made it possible to reduce the level of grain losses (according to the indicator of the serial control system on 7…15% by reduce the intensity of losses), which is especially effective in areas infested with weeds.